Religious Discourse on Gender Identity: Freedom of Expression or Hate Speech? A European Perspective - Montserrat Gas-Aixendri (Religions)
This paper explores the complexities arising from the intersection of religious freedom and the principles of gender equality and non-discrimination, a pressing issue within the modern European landscape. It investigates these challenges by examining legal responses to religious speech linked to gender identity, particularly in cases categorized as hate speech under criminal law. Through an analysis of jurisprudence and relevant legal and institutional frameworks, the study highlights the risks of relying on criminal law to address such disputes, including potential misuse and overreach. It critically assesses the appropriateness and impact of criminal sanctions, noting their potential to deepen societal divisions and intensify polarization. Moving beyond punitive measures, the article advocates for alternative approaches to resolving these conflicts, emphasizing dialogue, mutual understanding, and respect as means to reduce tensions and build more inclusive communities. By integrating legal analysis with broader societal perspectives, this study makes a meaningful contribution to ongoing debates. It examines how fundamental rights can be effectively reconciled within pluralistic and democratic societies.